Non-RGD peptide H-ckrwwkwirw-NH2 grafting accentuates antibacterial and osteoinductive properties of biopolymer coating. Issue 4 (1st October 2020) - Lin, Hsin-Yi; Chiou, Wei-Shang; Shiue, Sheng-Jie; Cheng, Jen-Kun
ABSTRACT: A coating on the surfaces of metallic implants to promote bone cell integration as well as prevent infection is highly desired for orthopedic surgeries. A novel antibacterial peptide was grafted onto an osteoinductive coating and the modified coating was tested for its antibacterial properties and biocompatibility with bone cells in vitro. A layer of chitosan hydrogel was chemically attached to the surface of a medical-grade titanium alloy and a novel non-RGD peptide (H-ckrwwkwirw-NH2 ) was grafted on top of the coating through chemical cross-linking. The composite layer was tested for its surface wettability (contact angle), composition (energy-dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy), antibacterial property, and bone cell biocompatibility. The successful grafting of the peptide onto the coating was confirmed by the increase of contact angle and nitrogen content (both p < .05) on the surface due to the presence of the hydrophobic amino acids. The modified coating successfully reduced the growth of Gram negative and positive ( E. coli and S. aureus ) bacteria by 74.2% and 52.4%, respectively ( p < .01). The coating did not show any sign of cytotoxicity and unexpectedly improved osteoblast proliferation and mineralization compared to unmodified samples (all p < .01). An antimicrobial peptide successfully grafted onto the chitosan coating to enhance its bactericidal function. This non-RGD peptide, after chemical modification, not only preserved its bactericidal activity but also improved the biocompatibility of the coating.